Exploration of Problems and Solutions of Islamic Education in the Millennial Era in an Ontological Review - Sholicha, Nikmatus; Muhammad Yusron Maulana El-Yunusi (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
Education This research aims to examine the problems of islamic educationin the millenial era through ontoligical observations. Ontology is the study of the nature of reality and existence. In the context of islamic education, ontological reflection is used to understand the nature and existence of the problems faced. The problems of islamic education in the millenial era are an important concern considering the continuing development of social, technological and cultural changes. This research uses a qualitative descriptive method, and uses primary data and secondary data. The technique used is using library research by reading related literature. The existing problems make it important to integrate islamic values into the curriculum as a response to changes in islamic values in the current context. This research has an important role for educational has a important role for educational practitioners, policy makers and the general public. By understanding the problems of islamic education in the millenial era, relevant and sustainable improvement efforts can be made to improve the quality of islamic education